Breakthrough by Breakdown: Metaphors and Structured Domains - Madsen, Kim Halskov (DAIMI Report Series, 1988)
In the daily situation of work, the members of an organization usually act without the need to disengage and reflect on their own tasks. But, in the design situation, it becomes important to talk about and reflect on the work. Moreover, it is crucial to set the proper structured domain appropriate for computerization. The message of this paper is that a breakthrough in design may be achieved by conscious use of metaphors. Metaphors may be used to break down the unreflected being of the members of an organization and metaphors may be used for setting of structured domains appropriate for computerization. The basic idea is to understand the organization in terms of other phenomena, whereby knowledge about these phenomena becomes a potential source of inspiration for designing new options. The paper builds its argument around a practical example as well as theoretical work on design and metaphors. The paper is concluded by a set of guidelines for metaphorical design.